Evidence for a mouse mesangial cell-derived factor that stimulates lymphocyte proliferation. - MacCarthy, E P (1985)
The functions of the glomerular mesangium are served by at least two populations of cells--a cell bearing microfilaments that regulates blood flow, and a phagocytic cell bearing Ia determinants and Fc receptors. We provide evidence that mouse mesangial cells (bearing microfilaments) produce a factor(s) that stimulates spleen cell proliferation. The factor(s) appears to act via monocytes/macrophages, since its stimulatory activity is abrogated by prior depletion of the responding mononuclear cell population of monocytes/macrophages. Confirmation of its action on macrophages was documented by experiments that showed that medium from macrophages incubated with mesangial cell supernatant contained greater amounts of a factor that stimulated [3H]thymidine uptake by macrophage-depleted spleen cell populations. By the cothymocyte proliferation assay, it could be shown that mesangial cell supernatant induced splenic macrophage production of interleukin-1-like activity. Preliminary characterization reveals the factor to have a molecular weight greater than 100,000. Thus, a novel function is delineated for this mesangial cell type that appears capable of modulating the local immune response by providing an amplification signal.